Development of Augmented Reality Learning Media as an Interactive Visual Educational Tool in Computer Component Learning - Dewiyanti, Intan; Firdaus, Rangga; Saputra, Bayu (Jurnal PPS-TP: Jurnal Pendidikan Analisis, Aplikasi Teori dan Hasil Penelitian, 2025)
Objectives: Computer component learning at MTs Negeri 1 Pringsewu still uses conventional methods (lectures, images, projectors) with limited interactivity. Laboratory conversion to classrooms restricts hands-on practice, resulting in low student interest and achievement (only 50% meet Minimum Completeness Criteria). Despite smartphone availability, Augmented Reality potential remains untapped. Prior Augmented Reality studies using Assemblr Studio have not developed targeted computer component media. This study aims to develop Augmented Reality-based learning media using Assemblr Studio to improve seventh-graders' understanding and interest. Methods: This study uses the Research and Development (R&D) approach with the 4D model (Define, Design, Develop, Disseminate). Findings: The developed Augmented Reality module was validated as highly valid (media expert: 92.5%, material expert: 100%), practical (100% teacher/student approval), and effective (N-Gain 0.9160, high category). The immersive media enhances engagement and knowledge retention while meeting educational standards. Conclusion: Findings demonstrate Augmented Reality’s potential to improve learning quality and expand educational technology applications. This media serves as a reference for future interactive learning innovations.